Konseling Kelompok dengan Pendekatan Realitas untuk Menangani Inner Child - Nisa, Afiatin; Utami, Sri; Renata, Dian; Satrianta, Hengki (Guidance : Jurnal Bimbingan dan Konseling, 2024)
In some literature, there are indications that the inner child has a negative impact if maintained. A solution is needed to reduce the negative impact of the inner child itself. Through a literature review, it is considered that group counseling with a reality approach is able to reduce the inner child in students. The purpose of this study was to test whether group counseling with a reality approach is able to reduce the inner child. This study is an experimental study with a time series design. The sample in this study were seven students who were selected purposively. Data were collected using the validated inner child scale technique and have a reliability that is worthy of being used as a research instrument. Data were analyzed nonparametrically through a sign test. The results of the study showed that group counseling with a reality approach was able to reduce the inner child. The results of this study are expected to be an additional reference in handling similar problems.